y = -2√x + Cx
Пошаговое объяснение:
Неоднородное уравнение первого порядка, решается заменой.
y = u*v; y' = u'*v + u*v'
u'*v + u*v' - u*v/x = 1/√x
u'*v + u*(v' - v/x) = 1/√x
Скобку приравниваем к 0
v' - v/x = 0
dv/dx = v/x
dv/v = dx/x
ln |v| = ln |x|
v = x
Подставляем в исходное уравнение
u'*v + u*0 = 1/√x
u'*x = 1/√x
u' = 1/(x√x) = x^(-3/2)
u = x^(-1/2) / (-1/2) + C = -2/√x + C
y = u*v = x*(-2/√x + C) = -2√x + Cx
y = -2√x + Cx
Пошаговое объяснение:
Неоднородное уравнение первого порядка, решается заменой.
y = u*v; y' = u'*v + u*v'
u'*v + u*v' - u*v/x = 1/√x
u'*v + u*(v' - v/x) = 1/√x
Скобку приравниваем к 0
v' - v/x = 0
dv/dx = v/x
dv/v = dx/x
ln |v| = ln |x|
v = x
Подставляем в исходное уравнение
u'*v + u*0 = 1/√x
u'*x = 1/√x
u' = 1/(x√x) = x^(-3/2)
u = x^(-1/2) / (-1/2) + C = -2/√x + C
y = u*v = x*(-2/√x + C) = -2√x + Cx